Navigating The Complexities Of Geriatric Oral Health: An Integrated Approach To Managing Xerostomia, Root Caries, And Tooth Wear - Loaloaa Mahmoud Al-Afandy, Shahad Samri Al-Anzi, Amal Mohammed Al-Omari, Nada Mohammed Al-Malawy, Shahd Abdullah Al-Karbi, Laila Mohammed Ahmed Awaji, Fatima Nabil Arnous, Amal Yahya Saleh Al-Zahrani; Haifa Mansour Hajjaj Al Marmash, Rania Hassan Ibrahim Hakami, Laila Hassan Mohammed Hamdi, Roaa Abdulaziz Al Dosari, Fatima Suwailek Mahmoud Al Shanqeeti, Najoud Khalaf Mohammed Al-Balawi (Journal of International Crisis and Risk Communication Research, 2024)
The global population is undergoing an unprecedented demographic shift, with a rapid increase in the number of older adults. Concurrently, advancements in dental care have led to a greater proportion of this cohort retaining their natural teeth into late life. This new reality has fundamentally altered the focus of geriatric dentistry, moving it from a model centered on managing tooth loss to one that addresses the complex oral health needs of a medically compromised, dentate population. Central to this new paradigm is the clinical triad of xerostomia, root caries, and pathological tooth wear—three interconnected conditions that frequently co-exist and create a synergistic cycle of oral deterioration. Xerostomia, or dry mouth, predominantly caused by polypharmacy and systemic diseases, acts as the nexus of this triad. By compromising saliva's protective functions—including lubrication, acid buffering, and remineralization—it significantly elevates the risk for both root caries and accelerates all forms of tooth wear. This review dissects the individual and synergistic pathophysiology of these three conditions within the physiological context of oral aging. It analyzes the evidence for contemporary diagnostic and management strategies, emphasizing a shift toward prevention, risk assessment, and minimally invasive interventions. A key conclusion is that effective management of this triad is not possible by treating each condition in isolation. Instead, this paper proposes an integrated clinical framework grounded in a comprehensive geriatric assessment that incorporates the patient's medical, functional, cognitive, and psychosocial status. This patient-centered approach necessitates an interdisciplinary team, including physicians, pharmacists, dietitians, and caregivers, to address the underlying etiological factors. Ultimately, this review serves as a call for a new standard of care, urging clinicians to adopt an integrated, preventive, and collaborative model to manage this destructive oral triad, thereby preserving function, enhancing comfort, and improving the overall quality of life for their aging patients.